Teachers’ Best Practices: A Phenomenological Philosophy - Jonifer Dultra (Newinera Publisher, 2022)
The purpose of this study is to explore the perceptions of teachers in the field in order to generate a theory from teachers’ best practices. This qualitative study utilized a survey questionnaire and followed a Straussian grounded-theory design to guide the coding and collection of interview data to identify emerging categories and generate such theory. The researcher had collected data through interviews with 15 respondents who are regular/permanent secondary school teachers. A constantant comparative analysis of the data were generated on teachers’ best practices theory. This emergent theory states that the perception of teachers’ practices will matter that there is great interest in educational leadership in the early part of the 21st century because of the widespread belief that the quality of leadership makes a significant difference to the school and student outcomes.